A prática educativa da mandiocada nas comunidades quilombolas Tabuleiro dos Negros e Sapé - Alagoas - Araújo, Laís Gois de (2019)
This research aimed to comprehend the transmission process of traditional knowledge through the cultural practice of the Mandiocada in the quilombolas remaining communities of Tabuleiro dos Negros and Sapé, located respectively in the cities of Penedo and Igreja Nova, in the state of Alagoas. We proceeded with the identification of the traditional knowledges that surrounded the quilombolas daily lives; the survey of the educational practices developed by the group in the transmission of these knowledges; and the analysis of the educational processes which are privileged by the subjects in the constitution of a quilombola identity. We identified the traditional knowledges regarding to the origins of the community; the farm production of subsistence derived from cultural practices as the Guerreiro and the Mandiocada; the use of medicinal plants; and religious and political traditional knowledges. We chose to focus our comprehension on the Mandiocada for its symbolic territoriality full of meanings which acess the ancestrality of the group. These knowledges were identified from our insertion in the territories we developed the research, through the reference of documents, observations and notes in the field journal and execution of semi-structured interviews. Our proposal is placed in a sensitive listening bias, from the voices of the communities’ subjects and their daily practices. Our conceptual plot embraces the notion of oral tradition cultures, the concepts of territoriality and ancestrality in afrobrazilian cultures, the subjectivity that crosses the phenomenom of the racism and the concept of decoloniality in the educational processes expressed by diasporical cultures of brazilian oral tradition cultures. The results allow us to identify the Mandiocada in the quilombola communities of Tabuleiro dos Negros (Penedo) and Sapé (Igreja Nova), in the state of Alagoas, as a cultural and pedagogical practice that communicates, through orality, knowledges of an entire ancestrality and african coletivity that builds itself by the bodies and the rituals. These traditional knowledges, belonging to a universalistic and dogmatic world view, may be part of the way to a decolonial and empowering practice of these quilombola groups.